Association between sleep quality and physical functioning in adults with Down syndrome: A brief report. Issue 1 (January 2022) - Bertapelli, Fabio; Johnson, Marquell; Pitetti, Ken; Smith, Mallory C.; Carlson, Benjamin; Curtis, Jasmine S.; Agiovlasitis, Stamatis
Abstract: Background: Sleep quality is associated with physical functioning in adults, but this has not been examined in those with Down syndrome (DS). High body mass index (BMI) and accelerated aging, both common in adults with DS, may alter the relationship between sleep quality and physical functioning in this population. Objective: To examine sleep quality indicators and its association with physical functioning in adults with DS, and whether associations are altered by BMI and age. Methods: Participants were 15 adults with DS (8 women; age 29 ± 14 years). We evaluated sleep quality over seven days with wrist-worn accelerometers and physical functioning with the timed-up-and-go (TUG) and 6-min walk (6 MW) tests. We examined the associations between sleep quality and physical functioning variables using Spearman's rho. Results: Sleep quality indicators were: total sleep time 407 ± 54 min; latency 26.8 ± 21 min; efficiency 73.9 ± 12 %; wake after sleep onset 122.8 ± 65.2 min; number of awakenings 21.0 ± 6.2; and average length of awakenings 6.1 ± 3 min. Total sleep time and average length of awakenings were significantly associated with 6 MW distances (rho = 0.58 and −0.69; p < 0.05, respectively). After controlling for age and BMI, 6 MW distance was significantly associated with total sleep time, latency, efficiency, and average length of awakenings (rho = 0.56, −0.73, 0.60, and −0.87; p < 0.05, respectively). TUG was significantly associated with total time in bed (rho = 0.71); p < 0.05). Conclusions: Sleep quality indicators are associated with walking performance in adults with DS. Age and BMI strengthen the relationship between sleep quality and physical functioning.